ENHANCING STUDENTS' COMMUNICATION SKILLS THROUGH TREFFINGER TEACHING MODEL - Alhaddad, Idrus; Kusumah, Yaya S.; Sabandar, Jozua; Dahlan, Jarnawi A. (Journal on Mathematics Education, 2015)
This research aims to investigate, compare, and describe the achievement and enhancement of students' mathematical communication skills (MCS). It based on the prior mathematical knowledge (PMK) category (high, medium and low) by using Treffinger models (TM) and conventional learning (CL). This research is an experimental study with the population of all students of Mathematics Education Department who took Discrete Mathematics subject matter of one university in the city of Ternate. The results show that (1) the achievement and enhancement of MCSÃ‚Â  students that usedÂ  TM are higher than the students learning using CL; (2) Based on the categories of PMK, the achievement and enhancement of MCS of students using TM are also higher than those learning with CL; and (3) There was no interaction effect between learning (TM and CL) and PMK to the achievement and enhancement of MCS of the students.Keyword: Communication Skills, Prior Mathematical Knowledge, Treffinger Model